2001
DOI: 10.1128/jb.183.24.7241-7252.2001
|View full text |Cite
|
Sign up to set email alerts
|

Improved Soybean Root Association of N-Starved Bradyrhizobium japonicum

Abstract: In this study, we addressed the effects of N limitation in Bradyrhizobium japonicum for its association with soybean roots. The wild-type strain LP 3001 grew for six generations with a growth rate of 1.2 day ؊1 in a minimal medium with 28 mM mannitol as the carbon source and with the N source [(NH 4 ) 2 SO 4 ] limited to only 20 M. Under these conditions, the glutamine synthetase (GS) activity was five to six times higher than in similar cultures grown with 1 or 0.1 mM (NH 4 ) 2 SO 4 . The NtrBC-inducible GSII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 55 publications
5
28
0
11
Order By: Relevance
“…1H). These results, in agreement with previous investigations (3,27,40), indicated that the microoxia and the stationary phase of oxic cultures were permissive conditions for PHB synthesis while the exponential phase of the oxic cultures was nonpermissive. In addition, the oxygen-limiting bacteroid state inside root nodules is also a permissive condition (3).…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…1H). These results, in agreement with previous investigations (3,27,40), indicated that the microoxia and the stationary phase of oxic cultures were permissive conditions for PHB synthesis while the exponential phase of the oxic cultures was nonpermissive. In addition, the oxygen-limiting bacteroid state inside root nodules is also a permissive condition (3).…”
Section: Methodssupporting
confidence: 93%
“…These results indicate that PhaR exerts its activity under conditions of oxygen limitation, in which accumulation of the substrates for PHB synthesis, similarly to reducing power and acetyl-CoA levels, may take place. In addition, the lack of PHB granules in our phaR mutant was accompanied by a higher production of EPS, a correlation previously observed in E. meliloti (16), R. etli (15), and N-limited B. diazoefficiens wild-type cultures (27,40). However, a plausible explanation of how phaR also controls EPS synthesis is lacking.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…When B. japonicum cells are cultured in N-starved media, the production of exopolysaccharides, capsular polysaccharides and the expression of nodC:lacZ is reduced, which results in the production of reduced nodule number by older cultures, or in delayed nodule formation in younger culture (Lopez-Garcia et al 2001 greenhouse experiments demonstrated that N-starvation during culture of an effective rhizobia strain did not enhance their competitiveness against an established and less competitive strain (Lopez-Garcia et al 2002), suggesting that number and position are more important than genetic/physiological aspects of competitiveness for inoculated strains. Using nod gene expression to indicate Nod factor production, Loh and Lopez-Garcia's experiments (Loh et al 2001;Lopez-Garcia et al 2001) demonstrated that although Nod factor production by a culture increased as cell density increased, production per cell decreased.…”
Section: Nod Factor Quorum Sensing and Its Relevance To Inoculant Promentioning
confidence: 99%
“…It is well known that legumes possess a systemic regulatory control able to detect the presence of combined nitrogen in the rhizosphere and block nodulation in response. Some publications (7,15,22), indicated that rhizobia nitrogen starvation has a positive influence on the symbiosis, leading to high N/C ratio and stimulating synthesis of surface polysaccharide, nod gene induction (19), all of which resulted in increased nodulation efficiency and competitiveness. Under carbon limitation, there is induction of a nonspecific attachment mechanism involving neither host plant lectins nor nod genes (31).…”
Section: Introductionmentioning
confidence: 99%